Adverse childhood experiences, recent negative life events, and non-suicidal self-injury among Chinese college students: the protective role of self-efficacy - Zixun Chen; JinWen Li; JinMeng Liu; Xia Liu (BMC, 2022)
Abstract Background Non-suicidal self-injury (NSSI) is a severe health problem closely related to adverse childhood experiences (ACEs). However, the underlying mechanisms by which ACEs may affect NSSI are largely unknown. Self-efficacy (NSSI-SE) and recent negative life events (RNLEs) may play important roles in this relationship. This study aimed to clarify the relationship between ACEs and NSSI among college students by examining the role of self-efficacy (NSSI-SE) and RNLEs in this process. Method Relevant self-report questionnaires were used to evaluate ACEs, RNLEs, NSSI-SE, and NSSI. A questionnaire of 1036 Chinese undergraduates (M age = 19.65, 28.9% males, 71.1% females) was collected in a cross-sectional manner. The associations between ACEs, RNLEs, NSSI-SE and NSSI were assessed using Pearson correlation analyses. Then, hierarchical multiple linear regressions were used to analyze the effects of ACEs and RNLEs on NSSI, as well as the protective effect of NSSI-SE on the above relations. Results NSSI was associated with both ACEs and RNLEs. ACEs and RNLEs could directly increase the risks of participating in NSSI, and the effects of ACEs and RNLEs on NSSI were independent without an interactive effect. NSSI-SE buffered the relationship between ACEs and NSSI, as well as between RNLEs and NSSI. Compared to individuals with a low level of NSSI-SE, ACEs and RNLEs were not significantly associated with NSSI in persons with a high level of NSSI-SE. Conclusion NSSI-SE may buffer the effect of ACEs and RNLEs on NSSI, indicating that future interventions can be enhanced by targeting NSSI-SE among college students with ACEs or RNLEs to prevent their engagement in NSSI.